2009
DOI: 10.3113/fai.2009.1233
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Fracture After Total Ankle Replacement: Surgical Technique

Abstract: Level of Evidence: V, Expert Opinion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
(5 reference statements)
0
4
1
Order By: Relevance
“…8 and Doet et al reported the prevalence to be 5% (Table 1). 5,9 Our case is different from previously reported cases in three aspects. First, the periprosthetic fracture in our case is the first reported case in which a Mobility  prosthesis was used.…”
contrasting
confidence: 96%
See 2 more Smart Citations
“…8 and Doet et al reported the prevalence to be 5% (Table 1). 5,9 Our case is different from previously reported cases in three aspects. First, the periprosthetic fracture in our case is the first reported case in which a Mobility  prosthesis was used.…”
contrasting
confidence: 96%
“…In the patient who received an AES prosthesis, the fracture developed due to a direct blow to the ankle. 9 In our case, the general condition of the patient was unremarkable, osteoporosis was not found intraoperatively, and a simple fall (minor trauma) led to the periprosthetic fracture. The authors hypothesize that the periprosthetic fracture may have resulted from the presence of a special tibial slot for component insertion and the unique design of the tibial component of Mobility  prostheses.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…With improvements in implant design and refinements of surgical technique, the intraoperative fracture rate has declined, but the number of postoperative periprosthetic ankle fractures appears to be increasing 8,9 . The existing body of literature describing periprosthetic ankle fractures is restricted primarily to case reports or small series, and to our knowledge there is no classification system clearly categorizing periprosthetic ankle fractures that could be used to guide fracture treatment.…”
mentioning
confidence: 99%
“…Not many other cases of fractures around a TAR have been published. Haendlmayer et al [ 18 ] presented a plate fixation of a tibial PF with a stable tibial component. In their discussion they cite 2 cases of distal tibial fractures around a TAR in which the tibial component was revised, reported as a podium presentation of which we found no published record.…”
Section: Discussionmentioning
confidence: 99%